(untitled) (Research, Society and Development, 2021)
The objective of this work is to evaluate the evolution of environmental legislation within the Brazilian historical and economic context. For this purpose, different historical periods of Brazil were analyzed: the period of ordinations, the imperial period of Brazil, the Old Republic, the republican period, the decades of 1930, 1960, 1970, 1980, 1990 and the two decades of the 21st century. Initially Brazil imported the first environmental protection laws of Portugal. In some historical moments, environmental protection should not sacrifice the country’s economic development, they constituted the main obstacles to the insertion of the sustainability component in the Brazilian economic development model. From the 1960s on, a season was started with good and advanced environmental devices, but ineffective, because the population did not yet have a sense of ownership and the appreciation of prevention and support of future generations. In the 1990s the legislation has integralizing characteristics, that is, it combines economic and social aspects with environmental aspects in order to preserve the Environment and meet the Federal Constitution. In the 21st century. XXI, with globalization, the global environmental pressure is to associate production, values and preservation of natural resources. This process of evolution of environmental legislation is a dynamic step and requires constant improvements, especially in the aspects of support for the implementation of legislation, such as supervision and technical staff of the managing bodies. Avoiding the setback is the greatest challenge in maintaining the constant evolution that the laws demand in the contemporary scenario.